2014
DOI: 10.1038/nm.3541
|View full text |Cite
|
Sign up to set email alerts
|

Tumor endothelium FasL establishes a selective immune barrier promoting tolerance in tumors

Abstract: We describe a novel mechanism regulating the tumor endothelial barrier and T cell homing to tumors. Selective expression of the death mediator Fas ligand (FasL/CD95L) was detected in the vasculature of many human and mouse solid tumors but not in normal vasculature, and in these tumors it was associated with scarce CD8+ infiltration and predominance of FoxP3+ T regulatory (Treg) cells. Tumor-derived vascular endothelial growth factor A (VEGF-A), interleukin 10 (IL-10) and prostaglandin E2 (PGE2) cooperatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
666
5
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 800 publications
(701 citation statements)
references
References 44 publications
21
666
5
9
Order By: Relevance
“…As a consequence, vascular normalization led to an improvement in antitumor T-lymphocyte trafficking and function, and mouse survival [74]. Finally, Motz et al recently showed that VEGF could induce Fas ligand (FasL) expression in tumor endothelial cells, which resulted in inhibition of CTL infiltration into tumors and reduced their cytotoxic activity [75]. …”
Section: Vegf Modulates T-cell Differentiation and Cytotoxic T-cell Funmentioning
confidence: 99%
“…As a consequence, vascular normalization led to an improvement in antitumor T-lymphocyte trafficking and function, and mouse survival [74]. Finally, Motz et al recently showed that VEGF could induce Fas ligand (FasL) expression in tumor endothelial cells, which resulted in inhibition of CTL infiltration into tumors and reduced their cytotoxic activity [75]. …”
Section: Vegf Modulates T-cell Differentiation and Cytotoxic T-cell Funmentioning
confidence: 99%
“…Thus, in these late stages the tumor micro-milieu may frustrate the effector arm of the immune system through different mechanisms. First of all, the influx of tumor-specific T-cells may be hampered by abnormal vascularization [25,26]. In both a xenograft transplant model and an immune refractory spontaneous murine model this problem could be overcome by treatment with low dose of gamma irradiation [25], or by targeting VEGF (vascular endothelial growth factor) [27].…”
Section: Treatment Of Advanced or End-stage Cancer May Fail Due To Immentioning
confidence: 99%
“…For example, it was recently shown that tumor endothelium can express FasL, which binds Fas (CD95) to induce cell death. Because cytotoxic CD8 + T cells have higher Fas expression than T regulatory cells (T regs ), FasL expression in the tumor endothelium was inversely correlated with CTL infiltration; such tumors respond better to cancer immunotherapy when used in combination with inhibitors of FasL (74). Thus, characterizing the tumor microenvironment is important for choosing the most promising immunotherapeutic strategies.…”
Section: Tumor Characterizationmentioning
confidence: 99%